Sexuality, sexual and reproductive health: an exploration of the knowledge, attitudes and beliefs of Greek-Cypriot adolescents - Kouta, Christiana (Middlesex University, 2003)
The study examines the knowledge, attitudes and beliefs of Greek-Cypriot adolescents regarding sexuality, sexual and reproductive health ίn Cyprus and is based οπ the concepts of culture, gender and sexuality under the general scope of health promotion and health education. The study reviews international and local literature οn the theory and practice of these ideas and their influence οπ health, focusing οn sexuality. Since culture and society are thought to influence health and sexuality, an extensive discussion is presented οn the history of Cyprus and its development ίn contemporary years. This is a Pan-Cyprian study of 697 third grade students (13-15 years old) ίn public general secondary (high) education schools (gymnasium) ίn Cyprus. Α close-ended questionnaire was designed including 51 questions. Three axes were taken ίn consideration: Knowledge; resources and needs; attitudes and beliefs. With the application of statistical analyses such as factor and cluster analysis, several results were drawn. Among other things the findings reveal that socio-cultural determinants such as religion/church, do have enormous impact οn Greek-Cypriot adolescents' attitudes and beliefs. Although young people do have some knowledge about sexuality, limited resources and services exist to support and reinforce that. in the Cypriot society of the 21st century some conservatism and taboo stiIl exist. Gender differences are apparent. Greek-Cypriot society at some point seems to have different expectations, roles and even a code of ethics' among males and females. Researching sexuality issues is a challenge since υρ until recently sexualίty was very much a taboo area. Contemporary Cypriot society is becoming more sensitive and open about it even though a degree of conservatism still exists.
Keywords: Reproductive health--Cyprus; Reproductive health--Greece; Sexuality; Adolescents; Σεξουαλικότητα; Έφηβοι